2012
DOI: 10.1039/c2sm25193k
|View full text |Cite
|
Sign up to set email alerts
|

How stereochemistry affects the physicochemical features of gemini surfactant based cationic liposomes

Abstract: The physicochemical features of mixed cationic liposomes formulated with 1,2-dimyristoyl-sn-glycero-3-phosphatidylcoline and one of three stereomeric cationic gemini surfactants were investigated by differential scanning calorimetry, fluorescence, TEM and dynamic laser light scattering. Actually, it was shown that the different stereochemistry of these gemini can strongly influence their capability of condensing and transfecting a plasmid DNA and of delivering a photosensitizer. The results obtained in this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Samples for TEM were prepared on copper grids covered with a carbon film. The vesicle dispersions were pipetted onto the grids and stained with 1% phosphotungstic acid (pH adjusted to 7.4) as performed in previous investigations [ 22 ]. Measurements were carried out by means of a FEI TECNAI 12 G2 Twin (FEI Company, Hillsboro, OR, USA), operating at 120 kV and equipped with an electron energy filter (Gatan image filter) and a slow-scan charge-coupled device camera (Gatan multiscan).…”
Section: Methodsmentioning
confidence: 99%
“…Samples for TEM were prepared on copper grids covered with a carbon film. The vesicle dispersions were pipetted onto the grids and stained with 1% phosphotungstic acid (pH adjusted to 7.4) as performed in previous investigations [ 22 ]. Measurements were carried out by means of a FEI TECNAI 12 G2 Twin (FEI Company, Hillsboro, OR, USA), operating at 120 kV and equipped with an electron energy filter (Gatan image filter) and a slow-scan charge-coupled device camera (Gatan multiscan).…”
Section: Methodsmentioning
confidence: 99%
“…Even stereochemistry of spacer affects their aggregation properties. Aleandri et al [25] studied mixed cationic liposomes formulated with 1,2-dimyristoyl-sn-glycero-3-phosphatidylcoline and three stereomeric forms of cationic gemini surfactant 2,3-dimethoxy-1,4-bis(N-hexadecyl-N,Ndimethylammonium) butane dibromide, by differential scanning calorimetry, fluorescence, TEM and dynamic laser light scattering. They found that different stereochemistry of these gemini strongly affect their capability of condensing and transfecting a plasmid DNA and of delivering a photosensitizer.…”
Section: Page 5 Of 33mentioning
confidence: 99%
“…A is the surface area of the head group. v and l c can be easily obtained using Tanford's formulas [52]: v = 27.4 +26.9n (25) l c = 1.54 + 1.265n (26) n is the number of carbon atoms present in the hydrophobic tails. As PL and gemini both have two tails in a molecule, the volume obtained for single tail was then doubled to get v. Therefore, R p value decreases and small micelles are formed.…”
Section: Interfacial Behavior Of Gemini:pl Mixturesmentioning
confidence: 99%
“…12 In fact, it is known that the uptake of caveolae-mediated endocytosis occurs at a much slower rate than that of clathrin-mediated endocytosis. 6 We know from a previous investigation 17 that DMPC/1a liposomes are characterized by a higher transition temperature and by a minor extent of lipid miscibility with respect to DMPC/1b liposomes. It was also found that DMPC/1a liposomes feature a surface potential, Ψ s , higher than DMPC/1b liposomes.…”
Section: Ultrastructural Investigationmentioning
confidence: 97%